Domination of Violations of the Principles of Cooperation in Conversations between Lecturers and Students in Lectures during the Covid-19 Pandemic - Afifah, Hanan Karunia; Rustono, Rustono; Santoso, B. Wahyudi Joko (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Communication between speakers and speech partners can be well established so that the purpose of the conversation can be fulfilled. However, when the purpose of the conversation is not fulfilled, a violation occurs. Conversational violations occur when the intent and/or purpose of the conversation does not occur. The purpose of this study is to review the dominance of violations of the principle of cooperation in conversations between lecturers and students in lectures during the co-19 pandemic. The approach used is pragmatic and descriptive qualitative approach. Data collection techniques using listening techniques, free listening, recording, and noting. The data were taken from conversations between lecturers and students during lectures on Youtube channels. The data analysis technique used is the lesap technique. The results showed that in the principle of cooperation there are four thimbles, namely the thimble of quantity, the thimble of quality, the thimble of relevance, and the thimble of manner. In the violation of the principle of cooperation, the quantity thimble dominates the other thimbles. The quantity thimble is violated more because lecturers often provide excessive information so that it is not in accordance with the context of the initial conversation. This makes the speaker's contribution exceed the information that should be needed by speech partners so that there is a violation of the principle of conversation.